Keterampilan Linguistik Bahasa Arab pada Mahasiswa Non Pesantren di Era Tradisi Digital - Ulil Albab (Tamaddun: Jurnal Kebudayaan dan Sastra Islam, 2022)
Writing skills are the highest of the other four language skills. Therefore, of course, writing skills have a variety of complex problems. This writing activity is the ability to think systematically, rationally and requires the ability to master vocabulary to put it in writing. This study analyzes how the ability to write Arabic is accompanied by an overview of the ability score possessed by students. This study aims to see the scores of students' Arabic writing ability, be it the average score, the lowest score and the highest score of writing Arabic in students of the Arabic language and literature study program. by using quantitative research methods that go from theory to the field to be tested for correctness and use purposive samples of students who are not from islamic boarding school backgrounds.This study aims to see the scores of students' Arabic writing ability, be it the average score, the lowest score and the highest score of writing Arabic in students of the Arabic language and literature study program. by using quantitative research methods that go from theory to the field to be tested for correctness and use purposive samples of students who are not from islamic boarding school backgrounds. The results of the study found that the ability to write Arabic in Arabic language and literature students was included in the low-ability category. From the two sample categories, first semester students got an average score of 16.59 and third semester students got a score of 12.66. In the language writing ability score, the highest score was 9.85 with the ability to write Arabic sound symbols. Then the lowest score of 0.19 on the ability to write characteristic letters using grammar on syntactic and morphological forms. Then the lowest score is obtained on the ability of students to write perfect sentences by including making the number of ismiyah and the number of mufidah with a score of 0.18. Another ability with the lowest score is the ability of students to write sentences with the use of comma punctuation and exclamation marks with a score of 0.19.